Hades and the Helm of Darkness - Holub, Joan; Williams, Suzanne, 1953- (Heroes in training, 2013)
"The Underworld usually isn't really meant to be a fun place - but tell that to Hades! He loves the dark and the stinky smell of sulfur. However, there is one thing that Hades is not a fan of: dogs. And when Zeus and his fellow Olympians encounter Cerberus - a snarling, three-headed dog - Hades must conquer his fears and tame the hound so everyone can continue into the Underworld and deposit their Titan prisoner, Oceanus, back where he belongs!"--Information from Amazon.com.